The Influence of Organizational Culture, Compensation and Organizational Commitment on Employee Performance through Job Satisfaction as an Intervening Variable at PT. Bank Muamalat Indonesia Makassar Branch - Aisyah Ulfah Imran (Scientia Human Capital and Organizational Behavior, 2023)
This study aims to determine the effect of organizational culture, organizational commitment, and compensation on employee performance from job satisfaction at PT. Bank Muamalat Indonesia Makassar Branch. The research describes the relationship and impact between the variables studied, using a quantitative approach. The sample in this research is 92 respondents. The research data collection method uses a questionnaire that is distributed offline. The data analysis technique used in this study is the structural equation model (SEM) which is operated from Smart PLS. The results of the study state that organizational culture, compensation and organizational commitment have a positive and significant effect on employee performance. Organizational culture, commitment and organizational compensation also have a significant and positive effect on job satisfaction. Likewise organizational culture, compensation and organizational commitment have a positive and significant effect on employee performance from job satisfaction .